Association between life’s essential 8 and risk of rheumatoid arthritis: a cross-sectional study - Longyun Wu; Jing Wang; Xueji Wang; Xuefeng Yue (BMC Rheumatology)
Abstract Objective To investigate the relationship between Life’s Essential 8 (LE8) and its individual constituents and the risk of rheumatoid arthritis (RA). Methods This cross-sectional study included participants aged 20 years and older from the NHANES database from 2005 to 2018. LE8 scores and scores for each of the LE8 components including diet, physical activity, nicotine exposure, sleep health, body mass index, lipids, blood glucose and blood pressure, were classified as cardiovascular health (CVH) scores of low (0–49), moderate (50–74), and high (75–100). Multivariate logistic regression was used to assess the association between LE8 scores and individual LE8 metric scores and the risk of RA. A curve-fitting model was used to assess the dose-response relationship between LE8 scores and RA risk. Results Of the 17,943 subjects (mean age: 46.10 ± 16.99 years; 48.33% males) included, 1233 were identified as having RA. After multivariate adjustment, participants with an intermediate or high LE8 score were associated with a reduced risk of RA compared to those with a low LE8 score (intermediate LE8 score: OR = 0.66, 95% CI = 0.62–0.71; high LE8 score: OR = 0.66, 95% CI = 0.62–0.71). Similar risk patterns were found for diet, nicotine exposure, sleep health, body mass index, and blood glucose. The dose-response relationship between LE8 score and RA risk was nonlinear. Conclusions Higher scores of CVH, assessed by Life’s Essential 8, were significantly associated with a lower risk of RA. Maintaining an ideal CVH score in the general population may be beneficial in preventing RA.